Exploring the sparsity of seismic wave propagation in complex media - Haindl, CM (2021)
Owing to continual improvements in computation power, we are getting closer to modelling seismic waves in ways that reflect the realistic complexity of the Earth. Nevertheless, modelling the true multi-scale structure of the Earth at large scale and/or high frequencies is currently still beyond our reach from a computational cost perspective. Hence, we rely on efficient modelling software to increase the scope of seismic simulations. Azimuthal Complexity Adaptation (ACA) is an innovative way of reducing the computational cost of seismic simulations by exploiting inherent sparsity of the wavefield. In this thesis, AxiSEM3D, an ACA-based modelling solver, is expanded to model wave propagation in local-scale settings. I find that the sparsity of wavefields persists in the presence of complex local-scale structures such as thrust faults and salt bodies and in models with full anisotropy. Further, I develop 3D wavefield scanning to locate complex areas of the wavefield and to investigate how they relate to structures in the subsurface model. The results suggest that high wavefield complexity is typically localised near abrupt wavespeed contrasts, on the low-wavespeed side thereof. I attempt to develop a new modelling solver which overcomes some of the limitations of AxiSEM3D. The resulting method is unstable, but it demonstrates the algorithmic complexity required to perform ACA in settings like coast lines. I conclude that a hybrid method which combines classic 3D modelling and ACA may be a simpler solution for increasing the scope of AxiSEM3D. Finally, I implement fault ruptures to simulate an earthquake scenario in the San Francisco Bay Area. Using ACA, I can include low-wavespeed bay muds which are usually neglected to save computational cost. Neglecting these muds leads to an underestimate of the shaking in the San Francisco Bay, even at low frequencies.